Different whole body HIIT protocols do not promote different muscle thickness and functional adaptations among healthy physically active subjects - Evangelista, Alexandre L.; de Camargo, Júlio B. B.; Rica, Roberta L.; Carnevali Júnior, Luiz Carlos; Mallett, Gregg S.; Bullo, Valentina; Bergamin, Marco; Gobbo, Stefano; Bocalini, Danilo S. (Frontiers in sports and active living, 2025)
Despite robust evidence on the benefits of high intensity interval training using body weight (WB-HIIT), the effects of different training configurations on morpho-functional adaptations are still unclear. Therefore, the aim of the present study was to assess the effects of two distinct WB-HIIT protocols on morphological and general fitness adaptations in healthy active young individuals. Thirty-four participants (22 males and 12 females) were randomly assigned to one of the following groups: 30 s of all-out effort interspersed with 10 s of passive recovery (G30 × 10, = 17) or 40 s of an all-out effort interspersed with 20 s of passive recovery (G40 × 20, = 17). Nine exercises were performed for both protocols, in two weekly sessions, during a 6-week intervention period. Morphological (ultrasound-derived muscle thickness of the vastus lateralis [MTVL]) and general fitness (muscle endurance and maximal oxygen consumption) assessments were performed at pre- and post-intervention moments. Both training protocols elicited significant improvements in all dependent variables ( < 0.05), with no significant between-group differences. Regardless of the training configuration, both WB-HIIT programs serve as time-efficient strategies to induce changes in muscle thickness of the vastus lateralis and functional adaptations in healthy, physically active young individuals.